2007
DOI: 10.3928/15428877-20070501-04
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive Sub-Tenon’s Anesthesia for Pars Plana Vitrectomy Under General Anesthesia: Is It Effective?

Abstract: <H4>BACKGROUND AND OBJECTIVES</H4> <P>To determine whether irrigation of the sub-Tenon’s space with anesthetic agents during pars plana vitrectomy (PPV) involving general anesthesia decreases postoperative pain, analgesic use, or nausea.</P> <H4>PATIENTS AND METHODS</H4> <P>A prospective, controlled trial of 46 consecutive patients requesting general anesthesia for PPV who were randomized to receive or not receive a sub-Tenon’s space injection prior to surgery. A mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2010
2010
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
3
1
Order By: Relevance
“…Contrary to the result of the current study, Mason et al [9] found that injection of sub-Tenon's space with local anesthetic drug prior to vitrectomy in generally anesthetized patients did not reduce postoperative pain or analgesic requirement. Furthermore, Ramachandran et al [10] have shown that sub-Tenon's block following general anesthesia did not reduce the incidence of postoperative pain after squint surgery in pediatric compared to IV fentanyl although there was a lower incidence of OCR and postoperative nausea and vomiting up to 2 h, but this may be due to the presence of emergence delirium that occurs with sevoflurane anesthesia and the use of Children's Hospital of Eastern Ontario Pain Scale which may not be capable of differentiation between emergence delirium and postoperative pain; this discrepancy in the results may be attributed to the use of another local anesthetic in different types of surgery.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to the result of the current study, Mason et al [9] found that injection of sub-Tenon's space with local anesthetic drug prior to vitrectomy in generally anesthetized patients did not reduce postoperative pain or analgesic requirement. Furthermore, Ramachandran et al [10] have shown that sub-Tenon's block following general anesthesia did not reduce the incidence of postoperative pain after squint surgery in pediatric compared to IV fentanyl although there was a lower incidence of OCR and postoperative nausea and vomiting up to 2 h, but this may be due to the presence of emergence delirium that occurs with sevoflurane anesthesia and the use of Children's Hospital of Eastern Ontario Pain Scale which may not be capable of differentiation between emergence delirium and postoperative pain; this discrepancy in the results may be attributed to the use of another local anesthetic in different types of surgery.…”
Section: Discussioncontrasting
confidence: 99%
“…Attempts have been made to reduce the dose of intraprocedural OA via different techniques of preventive analgesia for VRS, among which the most popular are regional techniques, including the preprocedural peribulbar block (PBB) [ 22 , 23 , 24 , 25 , 26 ], retrobulbar block (RBB) [ 27 , 28 ], subtendon block [ 29 , 30 ], and topical anaesthesia (TA) [ 31 ], as well as intravenous techniques, including preprocedural infusion of paracetamol [ 32 ] or metamizole [ 33 ]. A reduction in the intraprocedural intravenous dose of OA administered in combination with GA has been proven to provide adequate analgesia postoperatively [ 28 ], with reduced incidences of PONV [ 23 , 26 ], despite potential side effects [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, various methods of preventive analgesia (PA) for PPV, such as regional techniques [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], and intravenous techniques with preoperative infusion of COX-3 inhibitors (paracetamol, metamizole) [ 21 , 22 ], were shown to provide adequate postoperative analgesia [ 17 ], with a fall in the rate of main adverse events [ 12 , 15 , 23 ] within the mechanism of a reduction in demand for IO.…”
Section: Introductionmentioning
confidence: 99%